2010
DOI: 10.1002/ejic.201001122
|View full text |Cite
|
Sign up to set email alerts
|

New Access to and Reactions of P‐Functional Acylphosphane Complexes

Abstract: Keywords: Phosphanides / Phosphane ligands / Phosphaalkenes / Tungsten P-Functional (acylphosphane)tungsten complexes 4a-f have been prepared in good yields by the reaction of phosphinidenoid complexes 2a-d with acyl chlorides 3a,b. The reactions of acyl(chloro)phosphane complex 4a at -80°C with organolithium reagents selectively led to the formation of lithiated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…All the products 5a-d, 6, 7a-c, [10] 8, and 9 were fully characterized by multinuclear NMR, IR, MS, and elemental analysis. In addition, the structures of 5a ( Figure 4) and 6 ( Figure 5) were established unequivocally by X-ray crystal analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the products 5a-d, 6, 7a-c, [10] 8, and 9 were fully characterized by multinuclear NMR, IR, MS, and elemental analysis. In addition, the structures of 5a ( Figure 4) and 6 ( Figure 5) were established unequivocally by X-ray crystal analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this important NMR feature, they show markedly elongated C-E or Si-E bonds (E = Cl, O) in solid-state structures compared with their corresponding non-lithiated derivatives. Reactivity studies on Li/Cl (phosphinidenoid)tungsten complexes [R = CH(SiMe 3 ) 2 , C 5 Me 5 ] revealed nucleophilic reactivity towards organic iodides [9] and acyl chlorides, [10] and phosphinidene-like reactivity towards π-systems such as nitriles, alkynes, and aldehydes. Reactivity studies on Li/Cl (phosphinidenoid)tungsten complexes [R = CH(SiMe 3 ) 2 , C 5 Me 5 ] revealed nucleophilic reactivity towards organic iodides [9] and acyl chlorides, [10] and phosphinidene-like reactivity towards π-systems such as nitriles, alkynes, and aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and stability of chloroformylphosphane complexes 3a-c was found to be largely dependent on the nature of the substituents at phosphorus, the amounts of phosgene solution employed, and the temperature regime. When phosphinidenoid complex 2a [11] [X = Cl, R = CH(SiMe 3 ) 2 ] was reacted with nearly equimolar amounts of phosgene (20 % solution in toluene) in conditions similar to reported for preparation of analogous organylacylphosphane tungsten(0) complexes [12], no selective formation of the corresponding chloroformylphosphane complex 3a was observed. Instead, rapid formation of dichlorophosphane complex 1a [δ ( 31 P) = 157.6 ppm, 1 J P,W = 330.8 Hz] and some by-products assigned to the chloroformylphosphane complex 3a [δ ( 31 P) = 129.6 ppm, 1 J P,W = 296.3 Hz], chlorophosphane complex 4a [13] [δ ( 31 P) = 53.7 ppm, 1 J P,W = 268.8 Hz, 1 J P,H = 349.4 Hz], and nonidentified species was observed.…”
Section: Resultsmentioning
confidence: 98%
“…For example, 3a possesses a value inbetween those of the dichlorophosphane 1a and the corresponding benzoylphosphane complex [δ ( 31 P) = 113.8 ppm, 1 J P,W = 267.0 Hz] [12] in which the phenyl group is bonded to the carbonyl carbon instead of chlorine. In the 13 C NMR spectra signals of carbonyl carbon atoms of chloroformyl moieties for 3a and 3c were observed as a singlet (at -60 °C) and as a doublet [ 1 J(C,P) = 13.6 Hz; 25 °C] at 176.9 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%